2014
DOI: 10.1016/j.atmosenv.2014.05.049
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic organosulfates in atmospheric aerosols: Synthesis, characterization, and abundance

Abstract: Aromatic organosulfates are identified and quantified in fine particulate matter (PM2.5) from Lahore, Pakistan, Godavari, Nepal, and Pasadena, California. To support detection and quantification, authentic standards of phenyl sulfate, benzyl sulfate, 3-and 4-methylphenyl sulfate and 2-, 3-, and 4-methylbenzyl sulfate were synthesized. Authentic standards and aerosol samples were analyzed by ultra-performance liquid chromatography (UPLC) coupled to negative electrospray ionization (ESI) quadrupole time-of-fligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
113
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(119 citation statements)
references
References 37 publications
3
113
3
Order By: Relevance
“…However many challenges limit the application of LC/ESI-MS techniques, such as the lack of authentic standards for aromatic-derived organosulfates. 346 Future work should focus on synthesizing these compounds. Mass accuracy, on the other hand, strongly depends on various parameters including scan rate, signal-to-noise ratio, and resolving power of the instrument.…”
Section: E) Lc/ms and 2d-lc/msmentioning
confidence: 99%
“…However many challenges limit the application of LC/ESI-MS techniques, such as the lack of authentic standards for aromatic-derived organosulfates. 346 Future work should focus on synthesizing these compounds. Mass accuracy, on the other hand, strongly depends on various parameters including scan rate, signal-to-noise ratio, and resolving power of the instrument.…”
Section: E) Lc/ms and 2d-lc/msmentioning
confidence: 99%
“…However, quantification of organosulfates is a challenging task due to the lack of authentic standards and incomplete understanding of the sources, precursors and formation processes of organosulfates. To date, many studies of organosulfates have remained at the qualitative level, although a limited number of studies have provided quantitative or semi-quantitative analysis of certain organosulfates (e.g., Kundu et al, 2013;Staudt et al, 2014;Ma et al, 2014;Olson et al, 2011;Hettiyadura et al, 2017). Moreover, several studies show that organosulfates are present as a wide range of species with individual species such as the organosulfate derived from isoprene epoxydiols (IEPOXs) contributing 0.2-1.4 % of the total organic aerosol mass (Liao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Kundu et al (2013) quantified benzyl sulfate (C 7 H 7 SO − 4 ) and identified its homologous series with increasing number of methylene groups (C 8 H 9 SO − 4 and C 9 H 11 SO − 4 ) in Lahore, Pakistan. Furthermore, Staudt et al (2014) synthesized phenyl sulfate, benzyl sulfate, 3-and 4-methylphenyl sulfate and 2-, 3-, and 4-methylbenzyl sulfate and quantified them in aerosols collected in urban samples from Lahore and Pasadena, USA as well as Nepal. Ma et al (2014) reported the contribution up to 64 % from aromatic organosulfates to the sum of identified organosulfates during winter in Shanghai, while Wang et al (2016) found aromatic organosulfates to constitute less than 22 % of the detected number of organosulfates in Shanghai, Nanjing and Wuhan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative analyses of organosulfates in SOA have been gaining more attention and development in recent years (Lin et al, 2012;Shalamzari et al, 2013;Staudt et al, 2014). Riva et al (2015) investigated the formation of organosulfates from photooxidation of polycyclic aromatic hydrocarbons and found that, in the presence of sulfate aerosol, this photooxidation was a hitherto unrecognized source of anthropogenic secondary organosulfur compounds (Riva et al, 2015).…”
Section: Introductionmentioning
confidence: 99%